(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2024)
The release of models like ChatGPT from research labs has created new opportunities for personalized feedback and engagement in language instruction, aligning with the needs of foreign language learners seeking to enhance their English writing skills. This study examined the effectiveness of ChatGPT in improving English writing proficiency among Saudi undergraduate students and their perceptions and experiences of using ChatGPT. The research utilized a mixed-methods approach, incorporating experimental pre-and post-tests, semi-structured interviews, and open-ended questionnaires, which were analyzed using thematic analysis. The study comprised two phases: an interactive phase, where participants utilized ChatGPT for writing tasks and feedback, and an assessment phase involving pre- and post-intervention writing assessments. The findings revealed that the integration of ChatGPT into language learning positively impacted English writing proficiency, offering personalized support and feedback to learners. The results also underscore the potential of AI-powered learning tools in facilitating language development as captured by the positive perceptions and experiences of the participants. In conclusion, the results of this study suggested that ChatGPT could be effective in enhancing the writing proficiency of Saudi English as a foreign language (EFL) learner, and their perceptions and experiences provided valuable insights into the integration of ChatGPT into language learning.